Elective cesarean section on psychiatric indications - tokophobia - Korabiusz, Katarzyna; Wawryków, Agata; Stecko, Monika; Fabian-Danielewska, Anna; Harasimowicz, Joanna; Harasimowicz, Paweł; Torbé, Andrzej (Journal of Education, Health and Sport, 2019)
Aim of the study: The aim of the study was to analyze the influence of tokophobia on delivery solution by Caesarean section. The number of deliveries solved by Caesarean section has increased significantly in recent years. In Poland, it has almost doubled since 2000 (from 18.1% to 37%) Research methods: A survey was used in the study. 25 first-born girls and 25 multi-rivers took part, the selection criterion was delivered by caesarean section. Results: The fear of giving birth was the cause of caesarean section in 12 of the 25 primigravidas and 12 of the 25 multigravidas. Conclusion: Fear of childbirth may be a very important issue related to planning the delivery method.